Increased risk of venous thromboembolism in patients with brain tumors: A systematic review and meta-analysis. (January 2016) - Qian, Chunfa; Yan, Hua; Hu, Xinhua; Zhang, Wenbin; Liu, Hongyi
Abstract: Background: Currently published studies investigating the association between brain tumors and venous thromboembolism (VTE) risk have yielded inconsistent findings. To provide a more precise estimate for this association, we firstly performed a meta-analysis by pooling all currently available data. Methods: Pooled relative risks (RRs) with 95% confidence intervals (95% CIs) were calculated by use of STATA 12.0 software. All eligible studies were identified by a comprehensive literature search in databases of PubMed, Embase, Web of Science, and Google scholar. Results: According to the inclusion criteria, 9 independent studies were finally included into this study. Individuals with brain tumors were at an increased risk of VTE (RR = 1.66, 95% CI 1.31–2.12, P < 0.001), particularly those undergoing surgery (RR = 1.68, 95% CI 1.44–1.98, P < 0.001). Stratified analysis by type of tumor showed that the risk of VTE was significantly associated with glioma (RR = 1.68, 95% CI 1.44–1.98, P < 0.001), high-grade glioma (RR = 1.70, 95% CI 1.29–2.23, P < 0.001), and glioblastoma multiforme (RR = 1.74, 95% CI 1.43–2.12, P < 0.001). Conclusions: The present meta-analysis suggests increased risk of VTE in patients with brain tumors, particularly those undergoing surgery. Highlights: Increased risk of VTE related to brain tumors Increased risk of VTE for brain tumor patients undergoing surgeries Increased risk of VTE associated with glioma, high-grade glioma and glioblastoma multiforme